2019
DOI: 10.3390/cancers11091399
|View full text |Cite
|
Sign up to set email alerts
|

Matched Whole-Genome Sequencing (WGS) and Whole-Exome Sequencing (WES) of Tumor Tissue with Circulating Tumor DNA (ctDNA) Analysis: Complementary Modalities in Clinical Practice

Abstract: Tumor heterogeneity, especially intratumoral heterogeneity, is a primary reason for treatment failure. A single biopsy may not reflect the complete genomic architecture of the tumor needed to make therapeutic decisions. Circulating tumor DNA (ctDNA) is believed to overcome these limitations. We analyzed concordance between ctDNA and whole-exome sequencing/whole-genome sequencing (WES/WGS) of tumor samples from patients with breast (n = 12), gastrointestinal (n = 20), lung (n = 19), and other tumor types (n = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 50 publications
2
30
1
1
Order By: Relevance
“…We now report that ctDNA sequencing provides an accurate, albeit incomplete snapshot of the mutation profile and mutation burden of the patient-matched metastatic tumor. The SNVs found in the patient-matched melanoma gDNA and ctDNA overlapped by 22.7% to 77.6%, which is comparable to gDNA and ctDNA mutation concordance data reported for other cancers [9,10,12,31]. A major caveat of this work is the lack of patient-matched germline analyses, and although we applied a stringent bioinformatic filtering approach to enrich for somatic variants, the number of somatic variants and the concordance data may have been overestimated.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…We now report that ctDNA sequencing provides an accurate, albeit incomplete snapshot of the mutation profile and mutation burden of the patient-matched metastatic tumor. The SNVs found in the patient-matched melanoma gDNA and ctDNA overlapped by 22.7% to 77.6%, which is comparable to gDNA and ctDNA mutation concordance data reported for other cancers [9,10,12,31]. A major caveat of this work is the lack of patient-matched germline analyses, and although we applied a stringent bioinformatic filtering approach to enrich for somatic variants, the number of somatic variants and the concordance data may have been overestimated.…”
Section: Discussionsupporting
confidence: 67%
“…In our study, 9/10 patients received some sort of systemic treatment, and although melanoma has a very high TMB [38], the concordance between gDNA and ctDNA mutations was variable. Furthermore, although our cohort consisted of gDNA and ctDNA samples collected at different time points, the timing of sample collection was not associated with mutation concordance in our report and in another similar study [12].…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…Next-generation sequencing (NGS) technology has been widely used in molecular genetic research of various tumors 6 8 . Recently, a series of studies on the mutational landscape of ovarian cancer have been reported 9 , 10 .…”
Section: Introductionmentioning
confidence: 99%